Evidências de práticas de Controladoria e fatores contingenciais: estudo em empresas familiares no Estado do Ceará - Alves Júnior, Zacarias Pinheiro (2024)
This study aims to investigate whether there is evidence of a relationship between perceived contingency factors and the adoption of controlling practices in family businesses in the state of Ceará. The research has a qualitative approach, its nature is essentially descriptive and it is a field research carried out in 18 family businesses in the state of Ceará. Qualitative data were analyzed according to descriptive statistics. Companies consider the practices of the budget process, operational budget and tax planning to be very important/decisive, so much so that they are the most used by the organizations in the sample. The main factors that motivate the use of practices are the knowledge of the available internal team, commitment of those involved in the process, experience of the internal team, and what most restricts is not realizing the need to use the practices. In the view of the respondents, most organizations find themselves in a stable, differentiated environment dominated by a few organizations. Most organizations presented a mechanistic structure. The technology is standardized and has a database that offers sufficient support for decision making. The strategy they prioritize most is to develop a brand image that is much better than that of the competition. It is concluded that controlling practices are used by family businesses in the state of Ceará with a large percentage of adherence. Few practices are affected by contingency factors, as most practices have a membership percentage above 50%, but companies that are in a restricted environment have a low membership in the number of practices. When separated by contingency factors, a greater adherence to controlling practices was observed in groups of companies that are in a stable environment, in markets with little diversification, in a saturated environment, that have an organic operating structure, that have low technology to decision making. The relationship between practices and strategy has greater adherence in differentiation and in relation to the size of the company, greater adherence occurs in large companies.